Solve the system by substituting

Question

Asked 3/19/2012 6:49:47 PM

Updated 6/4/2014 8:26:06 AM

1 Answer/Comment

Flagged by yeswey [6/4/2014 8:21:53 AM]

Question

Asked 3/19/2012 6:49:47 PM

Updated 6/4/2014 8:26:06 AM

1 Answer/Comment

Flagged by yeswey [6/4/2014 8:21:53 AM]

Rating

3

2x+7y=27 rearranging the equation:

2x = 27-7y (equation 1)

2x-7y=-79 (equation 2)

institute 2x in equation 2 using equation 1 the result is:

(27-7y)-7y=-79

27-14y=-79

-14y=-79-27 = -106

y = -106/-14 = 53/7

2x = 27-7(53/7) = 27-53 = -26

x = -26/2 = -13

The solution for the system 2x+7y=27 and 2x-7y=-79 is (-13, 53/7)

2x = 27-7y (equation 1)

2x-7y=-79 (equation 2)

institute 2x in equation 2 using equation 1 the result is:

(27-7y)-7y=-79

27-14y=-79

-14y=-79-27 = -106

y = -106/-14 = 53/7

2x = 27-7(53/7) = 27-53 = -26

x = -26/2 = -13

The solution for the system 2x+7y=27 and 2x-7y=-79 is (-13, 53/7)

Added 6/4/2014 8:26:06 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [6/4/2014 12:37:58 PM]

31,260,400

questions answered

denyang

$216.05

Hearts 5,068 Views 1,505,687 Streams 600

phpmicro

$196.90

Hearts 4,014 Views 927,909 Streams 309

maydj

$194.15

Hearts 4,166 Views 1,108,648 Streams 414

sampi1890

$163.15

Hearts 4,447 Views 1,776,259 Streams 571

emdjay23

$152.05

Hearts 3,452 Views 837,892 Streams 267

miyaka

$150.25

Hearts 3,551 Views 914,049 Streams 468

Flora1988

$141.95

Hearts 3,385 Views 599,743 Streams 278

Peachygguk97

$139.05

Hearts 2,943 Views 388,718 Streams 192

There are no comments.